The diffusion and value of healthcare information technology - Bower, Anthony G. (Rand Corp., 2005)
This report characterizes the diffusion of use of electronic health records (EHRs). The author uses a series of interviews and surveys and an extensive literature review to investigate whether healthcare can duplicate the gains enabled by information technology seen in a number of prominent industries. To accomplish this, the report answers the following questions: What is the current diffusion of health information technology, especially EHR systems? How does EHR diffusion compare to innovations in other industries? What is such diffusion worth to society? And, what should the government do, if anything, to speed the adoption of EHR systems? The author finds that EHRs are diffusing at a rate consistent with other similar information technologies in other industries-rapidly in many segments of the healthcare industry yet more slowly in physicians' offices. Labor productivity increases are being seen and speeding adoption may be beneficial. The author provides a broad list of possible policy options that may be suitable for further study: Coordinate EHR standards immediately; work to improve quality measurement to encourage adoption and thereby alleviate the dauntingly labor-intensive process of quality management by using automation; reduce network externalities to encourage more, and more effective, adoption of EHR; encourage vigorous competition and deregulation; encourage firms to use health information technology as a competitive weapon; decide whether EHR is a societal goal and, if it is, provide subsidies; encourage government intervention in an incremental way, with rapid review of results to evaluate policies and strategies and adapt quickly.